Pectus Excavatum: A review of current treatment possibilities - Hedesz, Patryk; Taras, Andrzej; Woźniak, Kinga; Gardian-Baj, Monika; Jung, Magdalena; Jung, Maximilian; Żuk-Łapan, Aleksandra; Doryń, Aleksandra; Włodarczyk, Aleksandra; Popczyńska, Justyna (Journal of Education, Health and Sport, 2024)
Anterior chest wall depression known as Pectus excavatum (PE) , is currently the most common congenital chest wall deformation, with incidence estimated at 1/400 births, five times more frequently in boys than girls (5:1 ratio in occurrence). 1 Etiology of this deformity is formed by several hypothesis, including overgrowth of the ribs, developmental failure of the bony thorax or weakness and abnormal flexibility of the sternum. While theoretical concepts of its origin may differ, the common ground is the characteristics of said deformation: a posterior depression of the sternum and the lower costal cartilages. 2 Surgical treatment options were described since 1949 with Ravitch procedure and since then a number of new ones has been developed. For many years Ravitch and Nuss procedures were the main way to treat pectus excavatum, with a growing bias towards latter one. Since the Nuss procedure characterizes with less invasive approach and fever overall complications 3 its popularity outgrew Ravitch procedure and currently is described as MIRPE – Minimally Invasive Pectus Excavatum Repair. 4 However afterward then many new techniques were developed, focusing on reducing overall procedure risks, improving patient safety and quality of life and including new technical possibilities. The aim of this study was to gather and evaluate current literature to highlight new treatment options.